Regulation of the Dimerization and Activity of SARS-CoV-2 Main Protease through Reversible Glutathionylation of Cysteine 300 - Davis, David A.; Bulut, Haydar; Shrestha, Prabha; Yaparla, Amulya; Jaeger, Hannah K.; Hattori, Shin-ichiro; Wingfield, Paul T.; Mieyal, John J.; Mitsuya, Hiroaki; Yarchoan, Robert (mBio, 2021)
SARS-CoV-2 is responsible for the devastating COVID-19 pandemic. Therefore, it is imperative that we learn as much as we can about the biochemistry of the coronavirus proteins to inform development of therapy. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent for coronavirus disease 2019 (COVID-19), encodes two proteases required for replication. The main protease (M pro ), encoded as part of two polyproteins, pp1a and pp1ab, is responsible for 11 different cleavages of these viral polyproteins to produce mature proteins required for viral replication. M pro is therefore an attractive target for therapeutic interventions. Certain proteins in cells under oxidative stress undergo modification of reactive cysteines. We show M pro is susceptible to glutathionylation, leading to inhibition of dimerization and activity. Activity of glutathionylated M pro could be restored with reducing agents or glutaredoxin. Analytical studies demonstrated that glutathionylated M pro primarily exists as a monomer and that modification of a single cysteine with glutathione is sufficient to block dimerization and inhibit its activity. Gel filtration studies as well as analytical ultracentrifugation confirmed that glutathionylated M pro exists as a monomer. Tryptic and chymotryptic digestions of M pro as well as experiments using a C300S M pro mutant revealed that Cys300, which is located at the dimer interface, is a primary target of glutathionylation. Moreover, Cys300 is required for inhibition of activity upon M pro glutathionylation. These findings indicate that M pro dimerization and activity can be regulated through reversible glutathionylation of a non-active site cysteine, Cys300, which itself is not required for M pro activity, and provides a novel target for the development of agents to block M pro dimerization and activity. This feature of M pro may have relevance to the pathophysiology of SARS-CoV-2 and related bat coronaviruses. IMPORTANCE SARS-CoV-2 is responsible for the devastating COVID-19 pandemic. Therefore, it is imperative that we learn as much as we can about the biochemistry of the coronavirus proteins to inform development of therapy. One attractive target is the main protease (M pro ), a dimeric enzyme necessary for viral replication. Most work thus far developing M pro inhibitors has focused on the active site. Our work has revealed a regulatory mechanism for M pro activity through glutathionylation of a cysteine (Cys300) at the dimer interface, which can occur in cells under oxidative stress. Cys300 glutathionylation inhibits M pro activity by blocking its dimerization. This provides a novel accessible and reactive target for drug development. Moreover, this process may have implications for disease pathophysiology in humans and bats. It may be a mechanism by which SARS-CoV-2 has evolved to limit replication and avoid killing host bats when they are under oxidative stress during flight.